1999
DOI: 10.1002/(sici)1097-4644(19991201)75:3<481::aid-jcb12>3.3.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the kinase‐related protein gene found at human chromosome 3q21 in a multi‐gene cluster: Organization, expression, alternative splicing, and polymorphic marker

Abstract: We report the amino acid sequence, genomic organization, tissue expression, and alternative splice patterns for the human kinase related protein (KRP) gene, as well as the discovery of a new CA repeat sequence polymorphic marker in an upstream intron of the myosin light chain kinase (MLCK) gene. The KRP/MLCK genetic locus is a prototype for a recently discovered paradigm in which an independently regulated gene for a non-enzymic protein is embedded within a larger gene for a signal transduction enzyme, and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…There are distinct isoforms of MLCK (36,127,210,249). The skeletal muscle MLCK is the only tissue-specific MLCK, inasmuch as it is expressed in adult skeletal muscle, but not in cardiac, smooth, or nonmuscular tissues.…”
Section: Myosin Light-chain Kinasementioning
confidence: 99%
“…There are distinct isoforms of MLCK (36,127,210,249). The skeletal muscle MLCK is the only tissue-specific MLCK, inasmuch as it is expressed in adult skeletal muscle, but not in cardiac, smooth, or nonmuscular tissues.…”
Section: Myosin Light-chain Kinasementioning
confidence: 99%
“…Multiple MLCK isoforms are produced from the same MYLK gene by alternative splicing or alternative initiation (Lazar and Garcia, 1999;Verin et al, 1998b;Watterson et al, 1999). Six transcript variants have been identified that produce four kinase domainencoding isoforms and two isoforms of telokin.…”
Section: Transcriptionmentioning
confidence: 99%
“…The nmMLCK or smMLCK isoforms and telokin are ubiquitously expressed in various adult and fetal tissues and in cultured endothelium with qualitative expression appearing to be neither tissue-nor developmentspecific (Garcia et al, 1997a;Lazar and Garcia, 1999;Potier et al, 1995;Verin et al, 1998b;Watterson et al, 1999). The nmMLCK 1 and 2 isoforms are dominant isoforms in nonmuscle (endothelial) cells (Brown et al, 2010;Garcia et al, 1997a;Lazar and Garcia, 1999;Verin et al, 1998b).…”
Section: Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Northern blot analyses show that this MLCK-related gene expresses multiple transcripts, whose sizes ranges from 3.2 to greater than 18 kb (Kojima et al, 1996;Tohtong et al, 1997), but the structure of the transcription unit responsible for these transcripts has not been de®ned. In comparison, the chicken and human sm/nmMLCK genes also produce multiple transcripts, ranging from 2.7 to 9 kb in size, which in turn are translated into proteins whose size ranges from 17 to 210 kDa (Collinge et al, 1992;Watterson et al, 1995Watterson et al, , 1999Birukov et al, 1998). This``embedded gene'' concept enables a single transcription unit to produce several transcripts and protein isoforms via internal promoters and alternative translation starts (Watterson et al, 1995(Watterson et al, , 1999Birukov et al, 1998;Smith et al, 1998).…”
Section: Introductionmentioning
confidence: 99%